TEACHING PHYSICS BASED ON MODERN TECHNOLOGIES - Adashaliyeva FeruzaBonu (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes the teaching of physics and the problems that arise in it. It is clear that we will achieve new results as a result of studying and analyzing the problems. It was suggested that the development of pedagogical technologies should be effective in education and give the expected results.